Neuropsychological tests and prediction of dementia in association with the degree of carotid stenosis - Machaczka, Ondřej; Školoudík, David; Janoutová, Jana; Roubec, Martin; Reiterová, Eva; Kovalová, Martina; Zatloukalová, Anna; Ambroz, Petr; Janout, Vladimír (Journal of Applied Biomedicine, 2022)
This study constitutes a cross sectional analysis of the association between cognitive impairment defined by neuropsychological tests and carotid stenosis. The main objective was to compare the results of the Mini-Mental State Examination (MMSE) and Addenbrooke's Cognitive Examination-Revised (ACE-R) with regard to the degree of carotid stenosis. The sample comprised 744 patients who underwent a carotid duplex ultrasound and cognitive function testing (by ACE-R and MMSE). A multivariable analysis of potential confounding factors was completed. The significance of the different number of positive (MMSE ≤ 27, ACE-R ≤ 88) and negative (MMSE ≥ 28, ACE-R ≥ 89) results of the neuropsychological tests was analysed with regard to the degree of carotid stenosis (50-99%). Neuropsychological test results were also compared between carotid stenosis of 50-69%, 70-89%, and 90-99%. For both the MMSE and ACE-R, a difference was observed between positive and negative test results when higher degrees of stenosis were present. However, for the ACE-R only, more severe stenosis (80-89%, 90-99%) was predominantly associated with positive test results (p-value < 0.017). The same dependence for ACE-R (although not statistically significant) was observed in the group of patients without an ischemic stroke (confounding factor). In the case of the MMSE and more severe stenosis, negative results predominated, regardless of the confounding factor. There were no statistically significant differences in test results between carotid stenosis of 50-69%, 70-89%, and 90-99%. The results suggest that for assessing the early risk of cognitive impairment in patients with carotid atherosclerosis, the ACE-R appears more suitable than the MMSE.
Keywords: Dementia; stenóza arteria carotis; Cross-Sectional Studies; Humans; neuropsychologické testy; demence; Carotid Stenosis; Neuropsychological Tests; lidé; průřezové studie; Constriction, Pathologic; stenóza